Emergency obstetric care among referrals in more than 24 weeks gestation at a tertiary care teaching institution in Kerala, India - T., Heera Shenoy; T., Sheela Shenoy; K., Remash; Simon, Sony (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: One of the biggest barriers confronting efforts to reduce maternal mortality through increased skilled delivery is access to emergency obstetric care. This study aimed to look into the profile of emergency obstetric referrals. Referral-decision interval, reasons and morbidities of referral were analysed and their neonatal outcomes assessed. Methods: This observational study reviewed 90 emergency obstetric referrals over 3 years from June 2013 to February 2016. Results: In-labour referrals constituted the majority of emergency obstetric referrals. Preterm obstetric referrals needed emergency interventions in view of medical/obstetric indications and it was statistically significant. Referral- decision and referral-arrival interval was significant in emergency group (p-value-0.001). Babies born to mothers who were obstetric emergency referrals had extended NICU stay (p-value-0.001). There was a maternal death and four near-misses in this research. Conclusions: Timely decisions taken during interhospital emergency referrals resulted in better perinatal outcomes by prompt maternal interventions.